KEMAMPUAN MENDESAIN MEDIA PEMBELAJARAN INTERAKTIF PETH SIMULATION MATERI PECAHAN BERBASIS WEBSITE - Indriati Wardani, Theodora; Didik Purwosetiyono, FX; Riyanto, Riyanto (JIPETIK:Jurnal Ilmiah Penelitian Teknologi Informasi & Komputer, 2025)
The Digital Simulation course consists of both theoretical and practical components, where students must first master the theory before engaging in practice. Theoretical knowledge is delivered through lectures and supplemented with online weblog materials about designing interactive learning media using the Peth Simulation application, focusing on the topic of fractions, and utilizing a website platform. To design interactive learning media on fractions using the Peth Simulation application and Google Sites as the website, students must understand the software application. By mastering the procedures for designing web-based interactive learning media using Peth Simulation, students are expected to produce outputs in the form of images and text. The issue examined in this study is whether there is a significant difference in learning outcomes between students taught using a group discussion model and those without it. To address this issue, an experimental study was conducted at Universitas UPGRIS, specifically among fourth-semester undergraduate students majoring in Information Technology Education who were enrolled in the Digital Simulation course. The study involved one class, with an average of 32 students. A total of 30 students were selected as research subjects, divided into two groups of 15. Two types of data were collected in this study: (1) data from the group taught using group discussion regarding their ability to design web-based interactive learning media using Peth Simulation on the topic of fractions, and (2) data from the group without group discussion on the same task. The data were obtained through assignments and analyzed statistically using a t-test to determine the difference in learning outcomes between the two groups. The results of the t-test showed a significant difference in learning achievement, with the group that used the group discussion model performing significantly better in designing web-based interactive learning media using Peth Simulation on the topic of fractions than the group without group discussion.Keywords : Ability; Designing; Learning Media; Peth Simulation; Website.